Does Granting the Jordanian Government Exceptional Authorities in its Contracts Achieve the Economic Growth and Public Interest? - AL-SHIBLI, Farouq Saber (Journal of Advanced Research in Law and Economics, 2020)
Inadequate public funding and budgetary constraints are among the major problems that limit many governments’ abilities to finance infrastructure projects and offer services to the public. Recently many countries are seeking the involvement of their private sector through an agreement known as (administrative contract) to provide the public projects fund. The concept of administrative contracts is based on granting the government exceptional authorities that makes it the more powerful party in the contract and therefore capable of forcing contractors to carry out the public projects efficiently. Nevertheless, the private sector companies are not always willing to engage in a contract with the government, as there is a belief that the administration may misuse its exceptional privileges. The main objective of this paper is to examine methods available to guarantee the implementation of administrative contracts in a manner that achieves the best delivery of public services to the people from one hand, and to help the private sector to establish contracts with the government and provide them some guarantees for their investments from another hand. Accordingly, this article is based on the analytical legal research methodology to make a critical evaluation of the main obstacles facing administrative contracts in Jordan, and provide recommendations that may help avoiding the current prevailing issues.